MANAGEMENT OF FOETAL MUMMIFICATION THROUGH LEFT FLANK CAESAREAN SECTION IN CATTLE - SINGH, GYAN; KUMAR, SANDEEP; PRADEEP; Sukhbir; RAVISH; YADAV, RITU; RASHMI; ANUPAMA; SAINI, GITESH; HITESH (The Indian Journal of Animal Reproduction, 2021)
Mummification of the foetus is a rare gestational mishap that affects the majority of species of animals, including cows, with a rate of occurrence ranging from 0.13 to 1.8 per cent. The process of foetal mummification occurs about 70 days of gestation, after placentation and foetal ossification. However, the most common incidences of rd th were observed during the third to eighth month of pregnancy. Hematic mummification, is frequently referred to as chocolate mummification because a viscous brown-colored sticky substance covers the mummified foetuswhich is observed in cattle. A cow was presented to Veterinary Clinical Complex, (VCC), LUVAS, Hisar with history of prolonged gestation of 11.5 months and on per vaginal examination, cervix had one finger dilatation and hard in consistency with absorption of foetal fluids. The case was diagnosed as foetal mummification and mummified foetus was delivered by caesarean section through left flank.